Bias factors associated with assessing the validity of university teaching: a hierarchical linear model - Acevedo Alvarez, Raciel; Rodríguez, Nuria Mairena (Education Policy Analysis Archives, 2006)
The present study analyzes the variables that are intrinsically linked with the student, professor and class environment in relation to the university educational evaluation questionnaires. The participants in the study were 374 students with an age mean of 19.9 and 29 professors with an age mean of 36 from 3 different departments at the Universidad de Costa Rica (UCR) at the city of Guanacaste. The hierarchical lineal models were used for the data analysis, a quantitative methodology which facilitates the evaluation of the determinants which affect the results of the study. However, only four of these determinants were associated with the evaluation concerned, class size, enrolment year, department type and forecasted achievement levels. The results obtained from the study demonstrate that these kinds of evaluation are valid despite the results being slightly affected by a range of factors from externalities to teacher competence.